Fabricación de material compuesto de resina tipo UF y fibra de coco - Ochoa Avilés, Víctor Hugo (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
In the present work, the manufacture of a composite material of a Urea Formaldehyde (UF) synthetic resin combined with a coconut fiber was proposed. To achieve this, it was considered to determine the amount of each of the elements in a convenient way, under a forming procedure with adequate pressure, temperature and time factors, mechanical and physical characterization of the samples were obtained for their qualification. A minimum of 52 samples were obtained under the same process operating conditions, of which 50% were used for physical and mechanical characterization and the remaining 50%, for qualitative determination of the manufacturing quality of the samples. The results obtained, they qualify fabricated samples in a category of soft hardness and slight flexibility, It presents a property of resistance to deformation to swelling due to the action of water, feasible of 6.99%, where material deformation is minimal, Regarding the density calculation, it falls into the category of medium density of 0.4898gr/ cm3, that makes the manufactured composite material, in a possibility to be able to use and compete with standard commercial boards.

En el presente trabajo se planteó la fabricación de un material compuesto de una resina sintética Urea Formaldehido (UF) mezclada con una fibra de coco. Para lograrlo, se consideró determinar la cantidad de cada uno de los elementos de manera conveniente, bajo un procedimiento de conformado con factores de presión, temperatura y tiempo adecuados, se hizo caracterización mecánica y caracterización física de las muestras obtenidas para una calificación de las mismas, se obtuvo un mínimo de 52 muestras bajo mismas condiciones operativas del proceso, de las cuales el 50% se utilizaron para caracterización física y mecánica y el 50% restante, para determinación cualitativa de la calidad de la fabricación de las muestras. Los resultados obtenidos, califican a las muestras fabricadas en una categoría de dureza blanda y ligera resistencia a la flexión, presenta una propiedad de resistencia a la deformación por hinchamiento por acción del agua factible del 6.99%, donde es mínima la deformación del material, respecto al cálculo de densidad, cae en la categoría de media densidad 0.4898 kg/cm3. Lo que convierte al material compuesto fabricado, en una posibilidad de poder usar y competir con tableros comerciales estándar.
Facultad de Ingeniería Mecánica. Maestría Ciencias en Ingeniería Mecánica
Keywords: info:eu-repo/classification/cti/7; FIM-M-2023-1664; Material compuesto; Urea formaldehido; Caracterización mecánica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16789